Nanoscale air channel devices- inheritance and breakthrough of vacuum tube - Baihong Chen; Linjie Fan; Jinshun Bi; Zhiqiang Li; Ziming Xu; Sandip Majumdar (Nano Materials Science)
The nanoscale air channel device (NACD) has recently gained significant attention as a novel vacuum electronic that can be fabricated through nanofabrication technologies. Here, the research and progress of the NACD since it was reviewed, with a focus on working mechanism analysis, nanofabrication technologies, device structure optimization, electrode materials and simulation approach. Furthermore, the application fields and future development of NACD were summarized and prospected. The NACDs are expected to surpass the physical limits of traditional solid transistors due to its advantages such as smaller heat loss, high-speed, resistance to harsh environments.